2013
DOI: 10.3390/medicina49060045
|View full text |Cite
|
Sign up to set email alerts
|

Career Intentions and Dropout Causes Among Medical Students in Kazakhstan

Abstract: Background and Objective. The number of new entrants to higher medical schools of Kazakhstan increased by 1.6 times from 2007 to 2012. However, it is not known how it will affect the shortage of human resources for health. Additionally, human resources for health in rural areas of Kazakhstan are 4 times scarcer than in urban areas. The aim of the present study was to investigate the intentions of students toward their professional future and readiness to work in rural areas, as well as to determine the causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
4
5
0
Order By: Relevance
“…A study conducted in Kazakhstan identified a similar trend, with 4% of the participants expressing a desire to leave the medical profession altogether. 20 Additionally, again similar to our results, the study reported a pattern in which medical students in junior years were less inclined to express a desire to leave the profession compared with students in senior years. 20 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A study conducted in Kazakhstan identified a similar trend, with 4% of the participants expressing a desire to leave the medical profession altogether. 20 Additionally, again similar to our results, the study reported a pattern in which medical students in junior years were less inclined to express a desire to leave the profession compared with students in senior years. 20 …”
Section: Discussionsupporting
confidence: 89%
“… 20 Additionally, again similar to our results, the study reported a pattern in which medical students in junior years were less inclined to express a desire to leave the profession compared with students in senior years. 20 …”
Section: Discussionsupporting
confidence: 89%
“…The first concerns the academic performance of rural students at pre-higher education levels, where a relationship has been widely established between academic performance and higher education performance in terms of average grades (Bania and Kvernmo, 2016). As such, students who are better qualified in secondary school have a lower risk of dropping out at the tertiary level (Rapley et al, 2008;Faizullina et al, 2013;Hines et al, 2015;Lewine et al, 2019;De Hart and Venter, 2013), as well as those with high performance in specific subjects, as was the case for natural sciences in the medical school students analysed in the study by Faizullina et al (2013). The second subcategory is related to disciplinary knowledge prior to the training programme, where student desertion in the rural population is directly related to the knowledge acquired in secondary school in specific undergraduate subjects.…”
Section: Academic Determinantmentioning
confidence: 99%
“…This is due to a lack of information prior to the selection of the academic programme or family pressures (Pillay and Ngcobo, 2010). Faizullina et al (2013) reported that this variable is one of the main causes of dropout in medical schools in Kazakhstan. On the other hand, excessive academic work can lead to the phenomenon of dropout, as it competes in time with other student activities such as work and personal obligations imposed by their socioeconomic reality (Pillay and Ngcobo, 2010;Pérez et al, 2021).…”
Section: Academic Determinantmentioning
confidence: 99%
“…As two studies have reported in the past that financial problem has no significant role in the incidence of dropout thoughts among students (Arulampalam et al, 2004; Faizullina et al, 2013) in contrast the study of (Dyrbye et al, 2010) reported that debt is associated with future serious thoughts of dropping out. Having a chronic illness is not a significant factor in the study of (Faizullina et al, 2013), whereas opposite results were found in the studies of (Maher et al, 2013; Stetto et al, 2004). As stated above, student’s accommodation (either in the campus, with family or with friends) was not found as a significant factor.…”
Section: Discussionmentioning
confidence: 85%